The various faces of vulnerability: offering neurointerventions to criminal offenders - Ligthart, S; Dore-Horgan, E; Meynen, G (Oxford University Press, 2023)
In recent years, we have witnessed considerable progress in neurotechnologies that visualize or alter a person’s brain and mental features. In the near future, some of these technologies could possibly be used to change neural parameters of high-risk behavior in criminal offenders, often referred to as neurointerventions. The idea of delivering neurointerventions to criminal justice populations has raised fundamental normative concerns, but some authors have argued that offering neurointerventions to convicted offenders could be permissible. However, such offers raise normative concerns too. One prominent worry that is often emphasized in the literature, relates to the vulnerability of convicted offenders in prison and forensic patients in mental health facilities. In this paper, we aim to show that as far as vulnerability is considered relevant within the context of offering medical interventions to offenders, it could contribute to arguments against as well as in favor of these offers.